2008
DOI: 10.1111/j.1399-5618.2008.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cerebrospinal fluid glucose metabolites to MRI deep white matter hyperintensities and treatment resistance in bipolar disorder patients

Abstract: Objectives Both diabetes mellitus and magnetic resonance image (MRI) deep white matter hyperintensities (WMHs) are more common in bipolar disorder (BD) patients than in matched controls. Deep—as opposed to periventricular—WMHs and diabetes are associated with treatment resistance and poorer outcome. This study investigated whether brain glucose metabolism by the polyol pathway—a pathway linked to nervous tissue disease in diabetes—is related to deep WMH volume and treatment resistance in BD patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 75 publications
(88 reference statements)
0
37
0
1
Order By: Relevance
“…An increased number and/or severity of white matter hyperintensities (WMH), which are hyper-intense bright spots that may be detected in T2-weighted and fluid-attenuated inversion recovery (FLAIR) MR images, is one of the most consistently reported abnormalities in bipolar disorder (Ahn et al, 2004; Altshuler et al, 1995; Aylward et al, 1994; de Asis et al, 2006; Dupont et al, 1990; Dupont et al, 1995; Figiel et al, 1991; Gulseren et al, 2006; Kempton et al, 2008; Lloyd et al, 2009; Lyoo et al, 2002; McDonald et al, 1991; McDonald et al,1999; Moore et al, 2001a; Moore et al, 2001b; Pillai et al, 2002; Regenold et al, 2008; Silverstone et al, 2003; Swayze et al, 1990; Tamashiro et al, 2008; Woods et al, 1995), although several negative reports have appeared (Botteron et al, 1995; Breeze et al, 2003; Brown et al, 1992; Chang et al, 2005; Dolan et al, 1990; Krabbendam et al, 2000; Lewine et al, 1995; López-Larson et al, 2002; Persuad et al, 1997; Sassi et al, 2003; Strakowski et al, 1993b; Zanetti et al, 2008). Regarding these negative findings, however, Ahn et al (2004) have pointed out that studies using thinner MR imaging slices, a larger sample size, and that have rated the severity of WMH, in addition to their presence or absence according to an established rating scale, tend to produce more consistent, positive results.…”
Section: Evidence From Neuroimaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased number and/or severity of white matter hyperintensities (WMH), which are hyper-intense bright spots that may be detected in T2-weighted and fluid-attenuated inversion recovery (FLAIR) MR images, is one of the most consistently reported abnormalities in bipolar disorder (Ahn et al, 2004; Altshuler et al, 1995; Aylward et al, 1994; de Asis et al, 2006; Dupont et al, 1990; Dupont et al, 1995; Figiel et al, 1991; Gulseren et al, 2006; Kempton et al, 2008; Lloyd et al, 2009; Lyoo et al, 2002; McDonald et al, 1991; McDonald et al,1999; Moore et al, 2001a; Moore et al, 2001b; Pillai et al, 2002; Regenold et al, 2008; Silverstone et al, 2003; Swayze et al, 1990; Tamashiro et al, 2008; Woods et al, 1995), although several negative reports have appeared (Botteron et al, 1995; Breeze et al, 2003; Brown et al, 1992; Chang et al, 2005; Dolan et al, 1990; Krabbendam et al, 2000; Lewine et al, 1995; López-Larson et al, 2002; Persuad et al, 1997; Sassi et al, 2003; Strakowski et al, 1993b; Zanetti et al, 2008). Regarding these negative findings, however, Ahn et al (2004) have pointed out that studies using thinner MR imaging slices, a larger sample size, and that have rated the severity of WMH, in addition to their presence or absence according to an established rating scale, tend to produce more consistent, positive results.…”
Section: Evidence From Neuroimaging Studiesmentioning
confidence: 99%
“…In unipolar depression (UD) and BD, increased deep WMH, but not necessarily periventricular WMH, have been frequently noted (Ahn et al, 2004; de Asis et al, 2006; Figiel et al, 1991; McDonald et al, 1999; Moore et al, 2001b; Regenold et al, 2008; Thomas et al, 2002a; Thomas et al, 2002b), although the opposite has also been reported (Altshuler et al, 1995). An association between increased rates of periventricular WMH and previous suicide attempts among patients with affective disorders has been reported (Pompili et al, 2008), suggesting that periventricular WMH may be potential neurological markers of suicidal behavior.…”
Section: Evidence From Neuroimaging Studiesmentioning
confidence: 99%
“…Neuroimaging research in BD has already produced several data documenting the involvement of different cortical and subcortical regions in different phases of the illness. In particular, published studies explored structural and functional abnormalities present in BD and tried to establish specific correlations with outcome (Moore et al, 2001;Wingo et al, 2009) as well as difficult-to-treat conditions such as treatment resistant forms (Regenold et al, 2008). The possibility to study cognitive function in BD through fMRI represents another major acquisition of neuroimaging in psychiatric research.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography studies show resting prefrontal hypometabolism and simultaneous resting limbic/paralimbic hypermetabolism in patients with bipolar disorder [6,7]. Nuclear magnetic resonance studies have revealed significantly elevated concentrations of sorbitol and fructose in the cerebrospinal fluid [8] and lower levels of N-acetylaspartate in frontal lobe structures and hippocampi [9,10]. Moreover, treatment with lithium increased levels of N-acetylaspartate in patients with bipolar disorder [11,12].…”
Section: Introductionmentioning
confidence: 99%